2011
DOI: 10.1167/iovs.10-5598
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Ocular Efficacy Profile of Mapracorat, a Novel Selective Glucocorticoid Receptor Agonist, in Rabbit Models of Ocular Disease

Abstract: BOL-303242-X shows full anti-inflammatory efficacy (similar to DEX) in experimental models of dry eye and postoperative inflammation while demonstrating reduced effects in IOP and body weight. These data indicate that mapracorat, a SEGRA, shows efficacy similar to that of traditional steroids while exhibiting an improved side effect profile in IOP and muscle wasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 54 publications
3
32
0
Order By: Relevance
“…It has been reported previously that, compared with traditional steroids such as dexamethasone, therapeutic doses of mapracorat elicit a reduced myocilin expression in TM cells by virtue of the partial agonist properties of this compound (57). It has also been reported previously that mapracorat shows full anti-inflammatory efficacy (similar to dexamethasone) in experimental models of dry eye and postoperative inflammation in rabbits while demonstrating reduced effects in IOP and body weight (55). Taken together, these data indicate that mapracorat, a selective glucocorticoid receptor agonist (SEGRA), shows efficacy similar to that of traditional steroids while exhibiting an improved side effect profile.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It has been reported previously that, compared with traditional steroids such as dexamethasone, therapeutic doses of mapracorat elicit a reduced myocilin expression in TM cells by virtue of the partial agonist properties of this compound (57). It has also been reported previously that mapracorat shows full anti-inflammatory efficacy (similar to dexamethasone) in experimental models of dry eye and postoperative inflammation in rabbits while demonstrating reduced effects in IOP and body weight (55). Taken together, these data indicate that mapracorat, a selective glucocorticoid receptor agonist (SEGRA), shows efficacy similar to that of traditional steroids while exhibiting an improved side effect profile.…”
Section: Discussionmentioning
confidence: 84%
“…A number of preclinical studies in both cultured cells and animal models have demonstrated that mapracorat is a potent antiinflammatory agent with limited side effects associated with traditional corticosteroids such as elevation of intraocular pressure (IOP) in ophthalmology (50,55,56). In vitro quantitative assays of myocilin expression in trabecular meshwork (TM) cells can be used for characterizing anti-inflammatory drugs that are glucocorticoid receptor (GR) ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Mapracorat treatment also decreased NF-kB and AP-1 activity (Cavet et al, 2010). In experimental models of dry eye and postoperative inflammation, mapracorat improved ocular inflammation similar to dexamethasone but demonstrated reduced effects in intraocular pressure and body weight Nuclear Receptors and Their Selective Modulators (Shafiee et al, 2011). Collectively, these data indicate that ZK-245186/BOL-303242/Mapracorat shows efficacy similar to that of traditional steroids while exhibiting improved side-effect profiles.…”
Section: Selective Glucocorticoid Receptor Modulatorsmentioning
confidence: 76%
“…Overexpression of myocilin protein in the trabecular meshwork is thought to play a role in steroid-induced glaucoma (Clark et al, 2001), and, consequently, mapracorat may have a more favorable therapeutic index than traditional GCs, owing to its reduced myocilin expression profile. Indeed, mapracorat was shown to have a decreased propensity to increase intraocular pressure in rabbits compared with dexamethasone (Shafiee et al, 2011). All of the above observations generate considerable interest in the development of this molecule as a novel anti-inflammatory agent for the treatment of steroid-responsive ophthalmic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1) is a novel selective glucocorticoid receptor agonist that has potent antiinflammatory properties in vitro and in vivo (Schäcke et al, 2009;Zhang et al, 2009;Cavet et al, 2010;Shafiee et al, 2011). Mapra-corat binds to the human GC receptor with an affinity comparable to that of dexamethasone (Schäcke et al, 2009).…”
Section: Introductionmentioning
confidence: 99%